Pemanfaatan limbah Tandan kosong kelapa Sawit Sebagai Bahan Baku Pembuatan Glukosa - Heri Pranoto (CHEMICA: Jurnal Teknik Kimia, 2016)
AbstractThe use of increase in plantation and production of crude palm oil (CPO), will be the more industrial waste generated. Based on statistics book published by DG oil palm plantations, the 2004 acreage of palm oil is 5.2 million hectares and in 2014 had reached 10.9 million hectares with a production of 29.3 million tons of CPO. One of the biggest wastes from palm oil mill is empty fruit bunches (EFB). During the utilization of empty fruit bunches just as boiler fuel, compost and as pavers in oil palm plantations. Though EFB potential to be developed into a more useful. One of them as raw material for making glucose. The process of creating glucose from empty fruit bunches, starts from the beginning that process of delignification treatment with NaOH solution of 17.5% followed by the hydrolysis using cellulase enzymes. The testing process on the study include is kappa test, lignin, cellulose and glucose test (through enzymatic hydrolysis process). The highest glucose obtained from the hydrolysis of the pH variation is at pH 5 and hydrolysis time 28hour with levels of 1.2% and for the greatest levels of temperature variation obtained at a temperature of 35 Â° C time hidolisis 28 hour with glucose levels of 1.2272% of each of dry weight (EFB).Keywords: Glucose; hydrolysis; EFB